Reinforcement on existing concrete that has been reinforced with CFRP : (Case study of a box culvert bridge on a Toll Road in Semarang, Indonesia) - Parang Sabdono; Sukamta (International Forum of Researchers and Lecturers, 2022)
Implementing a box culvert system on bridges is an economical choice due to the reduced material use. This system has a joint that blends between the slab and the abutment walls and pillars. With a stiffer joint, the moment that occurs is smaller than a simple beam system. Box culvert foundations are commonly shallow foundations. Consequently, it is vulnerable to settlement, particularly the abutments that receive soil loads from the bridge embankment. Therefore, making the displacement in the abutments greater than in the pillars. The existing box culvert structure at the study site in Semarang, Indonesia has a span of 2 x 15 meters. Reinforcement has been previously carried out using Carbon Fiber Reinforced Polymer (CFRP) to treat cracks. Though, as time passed, the treated cracks reopened and new cracks developed. Structural cracks occur at a negative moment, so that the reinforcement yielded. A reinforcement using CFRP does not increase stiffness—thus, a reinforcement with adding external reinforcement system is used. This reinforcement is done by adding 400 x 200 WF profile—connected mechanically by attaching anchors to the slab. Reinforcement with a WF profile is safer due to its mechanical system, which makes it easier to implement and monitor.